China has reached the Lewis turning point - Zhang, Xiaobo; Yang, Jin; Wang, Shenglin (International Food Policy Research Institute, 2010)
In the past several years, labor shortages in China have become an issue. However, there is heated debate as to whether China has passed the Lewis turning point and moved from a period of unlimited supply to a new era of labor shortage. Most empirical studies on this topic focus on estimation of total labor supply and demand. Yet the poor quality of China's labor statistics leaves the debate open. In this paper, China's position along the Lewis continuum is examined though primary surveys of wage rates, which offer a more reliable statistic than employment data. Our results show a clear rising trend in real wage rates since 2003. The acceleration of real wages even in slack seasons indicates that the era of surplus labor is over. This finding has important policy implications for China's future development.